The impact of R&D efficiency on economic growth in China: non-linear threshold effects - Liao, Chang-Sheng; Li, Xinyan (Technological and Economic Development of Economy, 2024)
This study uses a threshold estimation technique to examine whether the effect of R&D efficiency on economic growth in China differs according to the level of financial development. The results broadly confirm a nonlinear relationship between R&D efficiency and economic growth due to the dynamic and static threshold effects of financial development and R&D expenditure. This finding suggests that R&D efficiency does not significantly impact growth in the low and middle-financial development provinces at conventional levels. Hence, the benefit of R&D efficiency in China could stem from the positive effect of R&D in highly financially developed provinces. Though R&D efficiency is poor, R&D investment still enhances economic growth because the amount of R&D investment is enormous. This finding suggests that while it is most important to not unthinkingly expand R&D gross investment, it is also necessary to make full use of R&D investment by improving R&D efficiency.First published online 29 May 2024